2021
DOI: 10.1038/s41393-020-00599-w
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic stress disorder symptoms and pain intensity in persons with spinal cord injury

Abstract: Study design Cross-sectional.Objectives To examine the association between post-traumatic stress disorder (PTSD) symptoms and pain intensity, taking symptoms of anxiety and depression into account within persons with spinal cord injury (SCI). Setting Persons with SCI, who visited a Dutch rehabilitation centre between 2005 and 2010, were invited to complete a survey. Methods PTSD symptoms were measured with the Trauma Screening Questionnaire (TSQ), pain intensity with an 11-point Numerical Rating Scale (NRS), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…al. where individuals having higher PTSD symptoms were from primary/lower education background than with higher education [24]. Similarly, Tang et.…”
Section: Ptsd Prevalence and Predictorsmentioning
confidence: 77%
“…al. where individuals having higher PTSD symptoms were from primary/lower education background than with higher education [24]. Similarly, Tang et.…”
Section: Ptsd Prevalence and Predictorsmentioning
confidence: 77%
“…This may include, as two of the SCICs in the current study demonstrated, MDT colleagues administering psychological health screening. As identified in the Netherlands, screening enhanced non-psychologist rehabilitation members' appreciation of psychological issues [21]. Bombardier et al's (2021) comprehensive overview of screening and intervention includes guidance regarding how MDT colleagues can structure rehabilitation for those identified with mood difficulties and are highly applicable when qualified psychological resources are lacking [14].…”
Section: Discussionmentioning
confidence: 99%
“…The Netherlands commenced psychological screening in 2018, with inpatients being administered a range of brief measures within two weeks of admission as an inpatient or on commencing an outpatient rehabilitation programme. The programme aimed to evaluate 80% of the people identified; however, an audit found that due to staffing constraints and logistics, only 64% of patients completed the measures [21]. Developed as part of the screening, the programme adopted a national approach of flagging those needing follow-up, with patient responses on each measure being RAG (red, amber, green) rated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spinal cord injury (SCI) poses great psychosocial challenges for the person affected and requires a long-lasting adaptation process which is reflected, among other things, in an above-average mental morbidity (1)(2)(3)(4)(5). Social support in the sense of the bio-psycho-social model plays a major role in coping processes (6).…”
Section: Introductionmentioning
confidence: 99%